2022
DOI: 10.2147/ijgm.s364790
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Axial Length with Macular Microvascular Changes in Chinese Diabetic Retinopathy Patients

Abstract: Objective To use optical coherence tomography angiography (OCTA) to compare macular blood flow density, subfoveal choroidal thickness (SFCT) and outer retina thickness (ORT) in non-proliferative diabetic retinopathy (NPDR) patients with different axial length (AL). Methods Total 42 patients with NPDR with different eye axis were divided into three groups: group A: 22 mm≤AL<24 mm; group B: 24 mm≤AL<26 mm; group C: AL≥26 mm. Superficial capillary plexus (SCP) in the macul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that AL may affect the structure of the macular area ( 24 ). Therefore, we made statistical analysis and comparison on AL of each group.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that AL may affect the structure of the macular area ( 24 ). Therefore, we made statistical analysis and comparison on AL of each group.…”
Section: Resultsmentioning
confidence: 99%